Efficacy of surgical treatment in patients with trigeminal neuralgia secondary to multiple sclerosis: A prospective study of 18 cases with evaluation of outcome and complications by independent evaluators. (May 2023) - Worm, Jacob; Noory, Navid; Smilkov, Emil Andonov; Heinskou, Tone Bruvik; Andersen, Anne Sofie Schott; Springborg, Jacob Bertram; Rochat, Per; Frederiksen, Jette Lautrup; Bendtsen, Lars; Maarbjerg, Stine
Introduction: Medical treatments for trigeminal neuralgia secondary to multiple sclerosis have low efficacy and tolerability and scientific evidence regarding efficacy of neurosurgery is scarce. We aimed to assess neurosurgical outcome and complications in trigeminal neuralgia secondary to multiple sclerosis. Methods: Patients with trigeminal neuralgia secondary to multiple sclerosis who underwent microvascular decompression, glycerol rhizolysis or balloon compression were prospectively and consecutively included from 2012 to 2019. Preoperatively, we systematically obtained clinical characteristics and performed a 3.0 Tesla MRI. Follow-up at three, six and 12 months was performed by independent assessors. Results: We included 18 patients. Of the seven patients treated with microvascular decompression, two patients (29%) had an excellent outcome (both had neurovascular contact with morphological changes), three patients (43%) had a good outcome, one patient (14%) had treatment failure and one patient (14%) had a fatal outcome. Three patients (43%) had major complications. Of 11 patients treated with percutaneous procedures, seven patients (64%) had an excellent or good outcome with major complications in three patients (27%). Conclusion: Percutaneous procedures provided acceptable outcome and complication rates and should be offered to the majority of patients with trigeminal neuralgia secondary to multiple sclerosis who need surgery. Microvascular decompression is less effective and has a higher complication rate in trigeminal neuralgia secondary to multiple sclerosis compared to microvascular decompression in classical and idiopathic trigeminal neuralgia. Microvascular decompression should only be considered in patients with trigeminal neuralgia secondary to multiple sclerosis when they have neurovascular contact with morphological changes.